EFFECT OF NITROGEN AND WEED MANAGEMENT ON NUTRIENT UPTAKE BY WEEDS UNDER DIRECT SEEDED AEROBIC RICE - SEEMA; KRISHNA , MAYA; DEVI, M.THOI THOI (The Bioscan, 2014)
A field experiment was conducted to assess the effect of nitrogen and weed management practices on yield of rice and nutrient removal by the weeds under direct seeded aerobic rice. The result of the experiment indicate that increased Nitrogen level from 75 to 100 kg/ha had increased the grain yield significantly (5%) though further increase in nitrogen dose (125 kg/ha) increased the grain yield but that was found non-significant. With the increment of nitrogen dry matter accumulation by the plant also increased. Among weed management all the weed management practices were found to be equally effective in reducing the uptake of nutrient by weeds and producing higher grain yield as compare to weedy check. However maximum yield was obtained with the application of pre-emergence of pendimethalin @ 1.0 kg a.i. /ha+ BM+ 1HW at 60 DAS. Thus it can be concluded that 100 kg N/ha is sufficient for aerobic rice in which weeds can be managed by integration of chemical and cultural practices.